MANAJEMEN PENGENDALIAN MUTU LPD AL BAHJAH CIREBON - Ali, Syarif Muhd (ASCENT: Al-Bahjah Journal of Islamic Education Management, 2024)
This study aims to understand the concept of quality control in Islamic boarding schools, the implementation of quality control and its implications for Al-Bahjah Islamic boarding school. This research used a qualitative research method with a case study approach. Data collection was conducted by in-depth interviews, observation and documentation. The research informants were the Head of the Foundation, Head of the Boarding School, Head of Tarbiyah Division and several alumni of Al-Bahjah Boarding School. Data were analyzed by condensation, display, and verification analysis. Then checking the validity of the data using data source triangulation. In this study, researchers found several research results, first, the planning of the quality of education at Al-Bahjah Islamic Boarding School is fast but directed. Implementation of the quality of education at Al-Bahjah Islamic Boarding School from planning through: Monthly to annual meetings to determine the RAB and quality lesson plans during the KBM process, revise and evaluate to find out what factors are the supporters and obstacles in the previous year, provide solutions or input in an effort to improve quality for the coming year, and there is control from the institution in carrying out the quality of education. The high interest of the community in Al-Bahjah pesantren is an implication of good pesantren management, proselytizing by the human resources of Al-Bahjah pesantren to the community, and teachers who are qualified in their fields who are brought in from abroad.